(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Melanin-concentrating hormone (MCH) receptors (provisional nomenclature as recommended by NC-IUPHAR [31]) are activated by an endogenous nonadecameric cyclic peptide identical in humans and rats (DFDMLRCMLGRVYRPCWQV; mammalian MCH) generated from a precursor (PMCH, P20382), which also produces neuropeptide EI and neuropeptide GE.